Storytelling and Folklore as Cultural Immersion Tools in Foreign Language Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Storytelling and folklore have long been recognized as powerful tools for language learning, particularly for young learners. These methods provide contextualized exposure to language while immersing students in the cultural traditions of the target language. This article examines how storytelling and folklore contribute to foreign language acquisition, highlighting their role in fostering linguistic competence, cultural awareness, and cognitive engagement. Using examples from English and Uzbek folklore, we highlight best practices for incorporating these techniques into language instruction. Additionally, this article examines the psychological and pedagogical foundations of storytelling, its role in memory retention, and the integration of modern technological tools to maximize its effectiveness.